2021
DOI: 10.1093/zoolinnean/zlab049
|View full text |Cite
|
Sign up to set email alerts
|

Metric variation in the postcranial skeleton of ostriches,Struthio(Aves: Palaeognathae), with new data on extinct subspecies

Abstract: As a result of numerous fossil and subfossil finds of ostriches, there is great demand for a comprehensive osteometric dataset for the living species and subspecies of the genus Struthio. We meet this demand by providing a set of > 100 measurements for a sample of 18 sexed skeletons, including all living and recently extinct species and subspecies of ostriches. We provide the first mensural data for two extinct subspecies, the hitherto questioned Struthio camelus spatzi from north-western Africa and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 52 publications
2
19
0
Order By: Relevance
“…To do so, they coupled morphometrics and multivariate statistics with the observation of medullary bone, a sex-specific tissue present in bones of egg-laying female in archosaurians (Dacke et al, 1993;Schweitzer et al, 2005Schweitzer et al, , 2007Canoville et al, 2019). The same kind of sexual dimorphism was observed in modern birds like California gulls (Larus californicus) (Schnell et al, 1985) and in the two extant species of ostriches (Struthio c. camelus, S. c. molybdophanes), but with reversed proportions between males and females (Elzanowski and Louchart, 2022). Furthermore, (Duggan et al, 2015) demonstrated that young male domestic ducks (Anas platyrhynchos) had more laterally curved femora than females, and that this sexually dimorphic feature disappeared along ontogeny.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…To do so, they coupled morphometrics and multivariate statistics with the observation of medullary bone, a sex-specific tissue present in bones of egg-laying female in archosaurians (Dacke et al, 1993;Schweitzer et al, 2005Schweitzer et al, , 2007Canoville et al, 2019). The same kind of sexual dimorphism was observed in modern birds like California gulls (Larus californicus) (Schnell et al, 1985) and in the two extant species of ostriches (Struthio c. camelus, S. c. molybdophanes), but with reversed proportions between males and females (Elzanowski and Louchart, 2022). Furthermore, (Duggan et al, 2015) demonstrated that young male domestic ducks (Anas platyrhynchos) had more laterally curved femora than females, and that this sexually dimorphic feature disappeared along ontogeny.…”
Section: Discussionmentioning
confidence: 97%
“…However, Elzanowski & Louchart (2022) demonstrated that female ostriches had more robust limb bones but smaller average body size than males. This decoupling between size and shape dimorphism is concordant with our results and emphasizes that sexual dimorphism is not necessarily reflected by body size nor allometry between limb segments.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations